2021
DOI: 10.2147/ppa.s315369
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of Chronic Kidney Disease Among the Population of Saudi Arabia Evaluated Using a Validated Questionnaire: A Cross-Sectional Study

Abstract: Introduction Public knowledge and awareness regarding chronic kidney disease (CKD) is an important factor influencing the successful implementation of CKD prevention and screening programs. To the best of our knowledge, there are no studies conducted among the Saudi population to explore the public knowledge of CKD using a validated questionnaire. Hence, we explored the knowledge of CKD among the population of the Kingdom of Saudi using a validated questionnaire to determine the level of knowledge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(45 citation statements)
references
References 19 publications
(46 reference statements)
2
12
0
5
Order By: Relevance
“…Similarly, the perceived risk and perception of CKD risk factors was categorized as low (<20) and high (≥20). Respondents with high perceived risk or perception were coded “1” and those with low perceived risk or perception were coded “0.” As the main predictor variable, CKD knowledge generated a positive response to a series of knowledge questions generated from previous CKD knowledge surveys and its CKD risk factors [ 28 39 ]. CKD's knowledge and beliefs were assessed by asking about the types of KD (acute and chronic KD), how people get kidney problems, knowledge of CKD risk factors, and CKD's signs/symptoms.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, the perceived risk and perception of CKD risk factors was categorized as low (<20) and high (≥20). Respondents with high perceived risk or perception were coded “1” and those with low perceived risk or perception were coded “0.” As the main predictor variable, CKD knowledge generated a positive response to a series of knowledge questions generated from previous CKD knowledge surveys and its CKD risk factors [ 28 39 ]. CKD's knowledge and beliefs were assessed by asking about the types of KD (acute and chronic KD), how people get kidney problems, knowledge of CKD risk factors, and CKD's signs/symptoms.…”
Section: Methodsmentioning
confidence: 99%
“…Equally, in this study, the independent variable include age, education, marital status, religion, income, other sources of income, and ethnic group. Thus, age cohorts were recoded as younger adults [ 15 – 29 ], young adults [ 30 39 ], and middle-aged adults [ 40 – 49 , 52 ]. Education was recoded as no education, low education (primary and secondary), and high education (tertiary).…”
Section: Methodsmentioning
confidence: 99%
“…Our findings support the literature that determined better knowledge of CKD among older population. In a study conducted in Saudi Arabia, participants with a greater age showed a substantially higher CKD knowledge score [ 18 ]. The risk of cardiovascular and renal diseases increases with age and is associated with high rates of morbidity and mortality [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, another recent study from Saudi Arabia using a non-validated questionnaire found that more than half of the study population correctly identified HTN and DM as CKD risk factors [ 15 ]. Another study also found a deficiency of awareness about CKD among Saudis, with respondents from higher educational and economic backgrounds having much more information and those with CKD risk factors also had a better understanding of the condition [ 18 ]. Besides, Chow et al observed a lack of broad public knowledge on CKD and recommended future research in a population of high-risk individuals [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…At a global scale, the Global Burden of Disease (GBD) reported in 2015, CKD is an important cause of morbidity and mortality (Global Burden of Disease Study 2013 Collaborators, 2015; Global Chronic Kidney Disease Collaboration, 2020). According to the World Health Organization (WHO), there are around 850 million people who suffers from some form of CKD and furthermore reported that CKD is more prevalent in low to middle income countries rather than the high-income countries (Lorig et al, 1999 In Kingdom of Saudi Arabia (KSA), CKD is considered as one major public health issue (Al Rahbi & Al Salmi, 2020; Almutary et al, 2013;Almutary, 2021;Alobaidi, 2021;Alsuwaida et al, 2010). In a recent study conducted to Saudi population, an increasing incidence and prevalence of end stage kidney disease (ESKD) has been reported (Almutary et al, 2013;Almutary, 2021;Alsuwaida et al, 2010).…”
Section: Introductionmentioning
confidence: 99%